Pembangunan ekonomi pertanian digital dalam meningkatkan persaingan pasar secara global (studi kasus kabupaten bojonegoro) - Lestari, Anik Ika (Maliki Interdisciplinary Journal, 2024)
Considering the challenges of global competition and advancements in the era of digitization, a sustainable approach and education for the community, especially in rural areas, regarding information technology is crucial. The objective of this research is to analyze the development of digital technology in enhancing global competition through production efficiency, the development of superior products, wider market access, and increased farmers’ income in Bojonegoro Regency. The research utilizes a descriptive method with a qualitative approach, employing observations, interviews, documentation, and internet references. The research informants consist of individuals with relevant knowledge, information, and experience, including two employees from the Department of Agriculture, Food, and Fisheries of Bojonegoro Regency, ten farmers, and eight members of farmer groups. The research is conducted in Bojonegoro Regency, focusing on the agricultural, food, and fisheries sectors. The research findings indicate that the use of digital technology in agriculture has increased product competition among farmers in Bojonegoro and has also led to increased demand and price appreciation for agricultural products.